Prevalence of depression among older adults living in care homes in China: A systematic review and meta-analysis. (January 2022) - Tang, Tan; Jiang, Jianling; Tang, Xinfeng
Abstract: Objectives: Despite the large number of older adults living in care homes in China, the reported prevalence of depression in such settings has varied greatly, while its pooled overall prevalence has remained unknown. In response, our systematic review and meta-analysis were designed to provide accurate, comprehensive evidence of the prevalence of geriatric depression in care homes in China. Methods: Literature searches were conducted independently by two investigators in English- and Chinese-language databases from database inception through January 2020. The prevalence of depressive symptoms in late life was analyzed with a random effects model. Results: In 69 studies addressing older adults living in care homes in China, the pooled overall prevalence of depressive symptoms was 36.8% (95% CI, 32.7%–41.1%). Respective estimates for mild and moderate-to-severe depressive symptoms were 29.1% (95% CI, 25.2%–32.7%) and 9.1% (95% CI, 7.5%–11.0%). Subgroup analyses revealed significant differences in the prevalence of late-life depression in care homes according to the type of care home, the individual's socioeconomic status, and the measurement instrument(s) used. Meta-regression analysis indicated that the prevalence of late-life depression among older adults living in care homes generally rose from 1991 to 2019. Conclusions: Given the high prevalence of geriatric depression in China's care homes, future studies should examine its risk and protective factors in those settings.